2019
DOI: 10.1002/lno.11355
|View full text |Cite
|
Sign up to set email alerts
|

Taxon‐specific dark survival of diatoms and flagellates affects Arctic phytoplankton composition during the polar night and early spring

Abstract: Effects of prolonged darkness on Arctic phytoplankton composition were investigated with lab experiments and a pigment time series in Kongsfjorden, Spitsbergen (78 55 0 N). Chlorophyll a (Chl a), pigment composition, particulate organic carbon, cell numbers, and photosynthetic characteristics were studied in Arctic diatoms (Thalassiosira antarctica, Thalassiosira nordenskioeldii) and flagellates (Rhodomonas sp., Micromonas sp.) during 8 weeks of darkness and subsequent recovery in irradiance. Loss of photosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Indeed, flagellated phytoplankton pigments declined during autumn and winter, causing a pronounced increase in diatom relative abundance. This suggests survival of diatoms during prolonged darkness, which is in agreement with dark survival experiments with diatoms and flagellates (Smayda and Mitchell‐Innes 1974, van de van de Poll et al 2019). Apart from reducing phytoplankton irradiance exposure, the expanding mixed layer can also entrain diatoms from deeper water layers and the ocean floor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, flagellated phytoplankton pigments declined during autumn and winter, causing a pronounced increase in diatom relative abundance. This suggests survival of diatoms during prolonged darkness, which is in agreement with dark survival experiments with diatoms and flagellates (Smayda and Mitchell‐Innes 1974, van de van de Poll et al 2019). Apart from reducing phytoplankton irradiance exposure, the expanding mixed layer can also entrain diatoms from deeper water layers and the ocean floor.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, diatom relative abundance was in good agreement with independent observations of silicic acid concentrations. Previous research indicated that ratios of fucoxanthin and other marker pigments of diatoms and flagellates relative to Chl a were stable during 8 weeks of darkness (i.e., pigments declined equally, van de Poll et al 2019). Pigments and CHEMTAX based phytoplankton composition provide coarse information, with no resolution beyond the taxonomic level.…”
Section: Potential Bias and Limitationsmentioning
confidence: 99%
“…Diatoms are known for their efficient growth under low light and rapid responses to increasing light availability (Geider et al 1986; Fisher and Halsey 2016; Poll et al 2019). In our experiments, photoacclimation of the diatom T. pseudonana outpaced the green alga, D. tertiolecta , following the shift from high to low light.…”
Section: Discussionmentioning
confidence: 99%
“…Most research on photoacclimation has examined phytoplankton physiology under balanced growth (Laws and Bannister 1980; Fisher and Halsey 2016) or in response to rapid increases in light to understand mechanisms involved in photoprotection of photosynthetic reaction centers (Lavaud et al 2004; Zhu and Green 2010). On timescales ranging from seconds to hours, diatoms decrease NPQ and alter carbon allocation mechanisms to sustain growth under decreasing light and even after exposure to darkness (Lohr and Wilhelm 1999; Bailleul et al 2010; Poll et al 2019). Green algae also decrease NPQ capacity, and their growth rate can slow drastically following a shift from high light to low light conditions (LaRoche et al 1991).…”
mentioning
confidence: 99%
“…This includes crucial primary producers, such as Micromonas polaris, which were encountered as active at different depths of Arctic marine habitats during polar night [14]. Persistence of low levels of light-dependent biological processes in primary producers during polar night is likely due to the persistence and perhaps even maintenance of a functional photosynthetic apparatus kept ready to be activated once the light comes back [13], [30]. Therefore an overrepresentation of eukaryotic proteorhodopsins during polar night was rather unexpected, as bacterial proteorhodopsins are known to contribute to an alternative pathway to photosynthesis being the main contributors to harnessing solar energy in the ocean [82].…”
Section: Discussionmentioning
confidence: 99%